UJI DISTRIBUSI SEMPROTAN SPRAYER PESTISIDA DENGAN PATTERNATOR BERBASIS WATER LEVEL DETECTOR - Agus Dharmawan; Siswoyo Soekarno (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2020)
The research aimed to examine droplet distribution using a knapsack sprayer with a water level detector-based patternator. The tests consist of measuring spraying discharge, effective spray wide and height, droplet distribution pattern and area, and traveling speed. The sensor calibration showed that the system read the liquid volume in the container with R2 = 0.99 at a linear curve: y = 2.572 + 2.502x.  The spray discharge was 0.033 L/s. The optimal spray was at 60 cm-nozzle height with effective spray wide and height were 0.64 m and 0.344, respectively. The spray distribution pattern illustrated that nozzle height affected droplet areas. The traveling speed due to nozzle height at 40 to 70 cm was 0.29 to 0.58 m/s, and had a line-up tendency, whereas spraying capacity was declined 1298 to 562 L/Ha.Keywords: Spray distribution, patternator, sprayer, water level detector